2021
DOI: 10.2147/cmar.s312784
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Serum lncRNA HOTAIR Combined with Galectin-3 in Benign and Papillary Thyroid Carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is the most common type of thyroid cancer. LncRNA HOTAIR (HOx Transcript AntIsense RNA) and Galectin-3 are involved in PTC. This study explored the clinical effect of lncRNA HOTAIR/Galectin-3 on PTC patients. Methods: Subjects were assigned into PTC (160 cases) and benign thyroid tumor groups (150 cases). Fasting peripheral venous blood was collected. LncRNA HOTAIR/Galectin-3 expressions in serum were detected. Subjects were assigned into HOTAIR/Glactin-3 high/ low expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In our study, the plasma expression of HOTAIR biomarker was found to be significantly higher in the patients with malignant thyroid nodules than in the patients with benign thyroid lesions and the studied controls. Our result agreed with those of Li et al, 2021, 39 who reported higher serum expression of LncRNA HOTAIR in PTC patients than in patients with benign thyroid tumor.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the plasma expression of HOTAIR biomarker was found to be significantly higher in the patients with malignant thyroid nodules than in the patients with benign thyroid lesions and the studied controls. Our result agreed with those of Li et al, 2021, 39 who reported higher serum expression of LncRNA HOTAIR in PTC patients than in patients with benign thyroid tumor.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, there is a vital importance to Recently, lncRNA HOTAIR has been recognized as a practicable biomarker in patients with PTC. The HOTAIR expression in serum or in thyroid tissues collected via fine-needle aspiration biopsies can serve as one of useful markers to differentiate benign nodules and thyroid cancers [10,25]. HOTAIR expression was shown to be significantly increased in PTC tissues, positively correlated with the advanced PTC stages, and negatively associated with overall survival probability of PTC patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…HOTAIR (HOX Transcript Antisense Intergenic RNA), as one of the well-known lncRNAs, has recently been noted to possess potential roles in PTC. HOTAIR could be detected in serum and the levels might serve as a diagnostic value to distinguish thyroid benign nodule and PTC [10]. Also, PTC patients with lymph node metastasis have significantly higher serum HOTAIR levels than them without metastasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, the predictive value of CK-19 in PTC with LNM has not been confirmed. Gal-3 has a diagnostic sensitivity and specificity of 78.75% and 66.67%, for papillary thyroid cancer, respectively, 5 which is far from adequate for accurate diagnosis. Therefore, it is essential to identify novel valuable biomarkers for the treatment, diagnosis, and prognosis of PTC.…”
Section: Introductionmentioning
confidence: 98%